Femtosecond Structural Dynamics in VO2 during an Ultrafast Solid-Solid Phase Transition. - Cavalleri, A; Tóth, C; Siders, C; Squier, J; Ráksi, F; Forget, P; Kieffer, J (2001)
Femtosecond x-ray and visible pulses were used to probe structural and electronic dynamics during an optically driven, solid-solid phase transition in VO(2). For high interband electronic excitation (approximately 5 x 10(21) cm(-3)), a subpicosecond transformation into the high-T, rutile phase of the material is observed, simultaneous with an insulator-to-metal transition. The fast time scale observed suggests that, in this regime, the structural transition may not be thermally initiated.